2004
DOI: 10.1038/sj.emboj.7600237
|View full text |Cite
|
Sign up to set email alerts
|

A novel CDK5-dependent pathway for regulating GSK3 activity and kinesin-driven motility in neurons

Abstract: Neuronal transmission of information requires polarized distribution of membrane proteins within axonal compartments. Membrane proteins are synthesized and packaged in membrane‐bounded organelles (MBOs) in neuronal cell bodies and later transported to axons by microtubule‐dependent motor proteins. Molecular mechanisms underlying targeted delivery of MBOs to discrete axonal subdomains (i.e. nodes of Ranvier or presynaptic terminals) are poorly understood, but regulatory pathways for microtubule motors may be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
251
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(263 citation statements)
references
References 77 publications
10
251
2
Order By: Relevance
“…Lee et al [27] reported that the KCl-induced dephosphorylation of GSK3β in SH-SY5Y cells could be blocked by the PP1/PP2A inhibitor okadaic acid and the PP2B inhibitor cyclosporine A [27]. However, in that study, 30 nM okadaic acid was used, which is well above the IC50 values of okadaic acid for PP1 (10 nM) and PP2 (0.1 nM) [34], thus making okadaic acid a broadlyspecific phosphatase inhibitor. Therefore, it is likely that PP1 also is involved in dephosphorylating GSK3β following KCl treatment.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Lee et al [27] reported that the KCl-induced dephosphorylation of GSK3β in SH-SY5Y cells could be blocked by the PP1/PP2A inhibitor okadaic acid and the PP2B inhibitor cyclosporine A [27]. However, in that study, 30 nM okadaic acid was used, which is well above the IC50 values of okadaic acid for PP1 (10 nM) and PP2 (0.1 nM) [34], thus making okadaic acid a broadlyspecific phosphatase inhibitor. Therefore, it is likely that PP1 also is involved in dephosphorylating GSK3β following KCl treatment.…”
Section: Resultsmentioning
confidence: 88%
“…The regulation of Ser21/9 phosphorylation has been attributed to the actions of protein phosphatase-2A (PP2A) [40,43,27,38] and protein phosphatase-1 (PP1) [46,34,41]. The PP1 holoenzyme is comprised of a 37 kDa catalytic subunit which associates with inhibitory subunits and targeting subunits.…”
Section: Introductionmentioning
confidence: 99%
“…A number of different phosphotransferase activities are altered in brains of AD patients, AD animal models, and cell lines exposed to A␤. The list of abnormal kinase activities in AD is extensive, among them several unrelated serine/threonine protein kinases including GSK3 (23,29,30), p38 (31), JNK (31), cdk5 (32,33), and CK2 (34). Interestingly, many of these enzymes are involved in regulation of FAT (28,29).…”
Section: Oa␤-induced Fat Inhibition Results From Endogenous Ck2 Activmentioning
confidence: 99%
“…109 One must be aware, however, that the inhibition of cdk5 was accompanied by activation of GSK-3␤ in neuronal cell culture and that p35 knock-out mice revealed increased GSK-3␤ activity and tau phosphorylation. 110,111 Cdk5 inhibition can be achieved by active site-directed inhibitors, by 2,6,9-trisubstituted purines and aloisines, which are small-molecule inhibitors that interfere with the cdk5/p25 complex formation (Cdk5 inhibitory peptide [CIP]), and by calpain inhibitors, which prevent p25 generation. 101,112,113 The use of active site inhibitors is hampered by their lack of selectivity toward cdk5.…”
Section: Antiphosphorylation Strategiesmentioning
confidence: 99%